(untitled) (Community Based Medical Journal, 2024)
Vasculitis retinae (VR) is a potentially sight threatening inflammatory condition of eye which may occur as isolated intraocular disorder or in association with various systemic diseases. It may occur as an idiopathic condition, as a manifestation of infections or non-infectious auto immune disorders. Impractical or unthoughtful approach increases the burden of treatment cost because of long investigation list. This prospective, observational study was carried out at the National Institute of Ophthalmology & Hospital (NIOH), a tertiary specialized eye hospital, Dhaka, Bangladesh, between March 2020 and February 2021, which aims to determine the common aetiology of VR patients. A total of 45 patients of VR were prospectively examined and investigated thoroughly. The mean age of mean age of onset of disease was 29.5 years where 82.2% were male. Among the 72 eyes of 45 patients of vasculitis retinae, the most common aetiology was Eales disease (52.8%), followed by tubercular VR (33.3%). Other causes of VR found in the study were toxoplasmosis (8.3%), systemic lupus erythematosus (SLE) (2.8%) and sarcoidosis (2.8%). The most common cause of VR was found Eales disease followed by Tubercular VR. Although the study has the limitations of being cross sectional and hospital based, the information from the study can be used by the ophthalmologist while dealing with the VR patients. CBMJ 2024 July: vol. 13 no. 02 P: 192-197